INFLUENCE OF HEAVY METALS ON THE DEVELOPMENT OF CORN VARIETIES - Digarbaeva Assem Moldazhanovna; Kaliyeva Anar Nurgaiypovna; Kirshibayev Erlan Ahmetkaliuly; Bahtybaeva Maira Rinatovna (Academic Journal of Physical and Chemical Sciences, 2021)
Heavy metals are some of the most harmful chemicals in the environment today. Today, many scientists believe that the main factor that negatively affects the plant in saline conditions is the osmotic effect of salts. In conditions of soil salinity, the lack of plants causes dehydration of proteins, which negatively affects the physiological and biochemical processes of plants. Plants absorb heavy metals in different ways. It absorbs heavy metals from the soil through the roots and from the air through the stomata of the leaves, mainly through dust. The aim of the research is to study the influence of heavy metals on the physiological and biochemical processes of growth and development of maize varieties. The article presents the research results of the heavy metals influence on the elongation of seedlings and the synthesis of photosynthetic pigments during the germination of maize varieties. It is obvious that heavy metals affect the growth and plant development from the initial germination stage of corn kernels. The results of monitoring various effects of heavy metals on photosynthetic pigments are also presented. In addition, the length of the abovewater and underground parts of the biomass, the ratio of dry weight to actual weight is the heavy metals effect on plants. For example, the leaves turned dark green, the stems twisted, did not fully open and turned pink. Under the influence of heavy metals, plant development, metabolism and photosynthesis are disrupted, as well as the normal course of respiration and photosynthesis. According to the results obtained, the impact of heavy metals on maize varieties significantly inhibits the accumulation and growth of biomass. In particular, the processes of plant root growth are suppressed. Differences in the tolerance of different varieties of heavy metals can be explained by their varietal characteristics and genetic basis. Currently, there is a theoretical and practical interest in the identification of ion-resistant forms of heavy metals, their ability to detect and reveal their nature, the development of ways to increase the impact and resistance of heavy metals on plants. Formulating the results of the study, it was found that different heavy metals concentrations (CuSO4 and CdSO4) negatively affect the growth of corn varieties. This can be seen from the tables below (tables 1, 2, 3, 4).